2017
DOI: 10.1108/bij-12-2015-0122
|View full text |Cite
|
Sign up to set email alerts
|

Applying structural equation model to study the critical risks in ERP implementation in Indian retail

Abstract: Purpose In order to reduce the high failure rate of enterprise resource planning system (ERP) projects in Indian retail, project managers need to analyze and understand the impact of risk factor on ERP implementation. The purpose of this paper is to identify the key risk factors solely or primarily for the Indian retail sector. Furthermore, this study also analyzes the impact of risk factors in ERP implementation using the structural equation model (SEM) approach. “User risk,” “project management risk,” “techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 56 publications
(80 reference statements)
0
23
0
2
Order By: Relevance
“…Organizations usually face several risks in the implementation and effective utilization of information technology and systems. The most difficult of these risks which must be taken into consideration are related to the skills of users of these systems, like the inability of companies to recruit skilled people (Suwardy et al, 2003), or the difficulty in ensuring effective training for users of these systems (Garg and Khurana, 2017). As such, the training of users needs to be emphasized, as it leads to benefits in the implementation and utilization of information systems.…”
Section: Training Of Mas Usersmentioning
confidence: 99%
“…Organizations usually face several risks in the implementation and effective utilization of information technology and systems. The most difficult of these risks which must be taken into consideration are related to the skills of users of these systems, like the inability of companies to recruit skilled people (Suwardy et al, 2003), or the difficulty in ensuring effective training for users of these systems (Garg and Khurana, 2017). As such, the training of users needs to be emphasized, as it leads to benefits in the implementation and utilization of information systems.…”
Section: Training Of Mas Usersmentioning
confidence: 99%
“… The interviewed participants having the similar thoughts while asked for the selection of MIS, CRM, DSS and ERP system applicability in their organizations. It is found that most of the participants have selected ERP as their necessary IS in their business (Garg & Khurana, 2017) [18] .  The 80% of the total 70 management employees have been reviewed ERP as their first choice while 90% of operational employees have suggested it.…”
Section: Resultsmentioning
confidence: 99%
“…Model fit indices such as the comparative fit index (CFI), NFI, root mean square of error approximation (RMSEA) and Tucker-Lewis index (TLI), were selected to judge the model fit (Garg and Khurana, 2017;Satapathy, 2014;Bandyopadhyay and Roy, 2011). To obtain an acceptable fit, CFI, NFI, and TLI should be greater than 0.9, and RMSEA must be lower than 0.08 (Garg and Khurana, 2017). Figure 2 shows the summary of indices for the measurement model.…”
Section: Internal Organization's Forcesmentioning
confidence: 99%